Structural Tuning of Anion‐Templated Motifs with External Stimuli through Crystal‐to‐Crystal Transformation. Issue 4 (15th December 2016) - Singh, Ashutosh S.; Tiwari, Ranjay K.; Lee, Mandy M.; Behera, Jogendra N.; Sun, Shih‐Sheng; Chandrasekhar, V.
Abstract: Protonation of trans ‐1, 2‐bis(4‐pyridyl)ethylene (4, 4′‐bpe) with dilute sulfuric acid (33 %) afforded a protonated adduct [{4, 4′‐bpe⋅2 H + }2 HSO4 −2 SO4 −2 {H2 O}2 ] (1 ). The neighboring olefinic bond in1 is in a suitable range (3.931–4.064 Å) to undergo a photochemical [2+2] cycloaddition reaction. Upon irradiation with UV light (365 nm), 1 undergoes a molecular sliding involving the 4, 4′‐bpe⋅2 H + units, affording2, stabilized through OSO4 ⋅⋅⋅π interactions. Heating1 to 50° C leads to a 3D hydrogen‐bonded organic framework (HOF) (3 ). This process occurs through thermal dissociation of the bisulfate anion. Diffusion of iodine through the crystal lattice of1 and3 enables the reduction of sulfate to bisulfate, affording a 1D hydrogen‐bonded chain (4 ). Solid‐state 13 C CPMAS NMR, IR, DSC, and powder XRD studies further support stimuli‐responsive structural tuning through crystal‐to‐crystal transformation. All these conversions occur with significant translational and rotational movements along with a series of bond‐breaking and bond‐forming processes. Abstract : Group walk in the dense phase with weak legs : Molecules inside a crystal (see picture) are tightly packed and are sensitive to spatial disturbance, especially if packed together by weak hydrogen bonds. Depending on external stimuli, molecules can arrange into 1D polymeric chains, 2D polymeric sheets, and a 3D hydrogen‐bonded organic framework through crystal‐to‐crystal transformation.